Comparação das técnicas de aferição do plano oclusal da maxila utilizando a espátula de madeira e a régua de fox - Kurashige, José Carlos Kiyoshi (2011)
The concept of beauty is something very special and often times subjective, however we, cannot deny that having a smooth face with definite and symmetric is one of the items of beauty. The quest for harmony facial features and many of these paths is in orthognathic surgery that is performed in patients with skeletal deformities, dental, aiming to promote aesthetics, function and a correct occlusal relationship. For orthognathic surgery, facial analysis, aims to give the condition of preparation for the patient to undergo the surgical procedure. Since the horizontal reference line is among the most relevant factors to be used in the analysis, as determined jaw line of the frontal plane. It is considered normal when it is harmonically in the vertical plane aligned with the upper and lower face, however, when it begins to vary more than 2 mm to one side, the third is affected, damaging the facial plane. Therefore, the concept of modern orthognathic surgery aims to treat occlusion seeking an aesthetic result with balance, harmony and airway maintenance. To obtain these results is essential for facial analysis and objective measurement of facial deformities. Maxillofacial allow the surgeon to perform a diagnosis and precise treatment plan and give patients a realistic simulation of the cosmetic results of treatment in advance.The purpose of this study is to determine whether there are differences in the measurement of the maxillary occlusal plane using the rule of Fox and wooden spatula